PANDANGAN FILSAFAT ILMU TERHADAP AKUNTANSI SYARIAH - Rahmadieni, Risky Yuniar; Rohmah, Annisa Nur (Lisyabab : Jurnal Studi Islam dan Sosial, 2023)
ABSTRACT The concept of sharia accounting based on Surah Al-Baqarah verse 282 states that believers must record all unfinished events, know the time and explanation of these events, and have witnesses so as not to cause hatred. The order emphasizes the importance of accountability for commercial parties to be irrefutable, conflict-free and impartial. Islamic accounting related to the recording of financial reports and analysis of transactional data, a science has a specificity according to what (ontology), how (epistemology) and on what (axiology) knowledge is built. These three things are interconnected. In this paper the writing will explore the philosophical views of science on sharia accounting. This study examines the meaning of the philosophy of science from the three main components of the philosophy of science, namely. asiology, epistemology and ontology, to develop sharia accounting theory and practice. This study used a qualitative research method in the form of a library review. With Islamic Accounting, it will present many things in terms of calculations and thoughts, even the basis of which is of course different from conventional accounting. With an ontological, epistemological, and axiological view of philosophy, sharia accounting will be created with fair, wise and in accordance with Islamic law. Keywords: Sharia Accounting, Philosophy of Science